2021
DOI: 10.3390/chemosensors9050112
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Antiradical Properties of Some Examples of Flavonoids and Coumarins—Potentiometric Studies

Abstract: A comprehensive study of a range of flavonoids and coumarins is presented in this article. The work uses an approach that evaluates the activity of these compounds by various mechanisms: the electron transfer (ET), the hydrogen atom transfer (HAT), and the mechanism of metal chelation. The studies were carried out using the methods of the cyclic voltammetry and the potentiometry. The electrochemical behavior of these compounds was studied by the method of cyclic voltammetry; the main types of voltammograms, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 61 publications
(151 reference statements)
1
9
0
Order By: Relevance
“…The value of the antiradical capacity was found to reflect the antioxidant properties based on the hydrogen atom transfer mechanism [40,41,56,57]. A number of valuable patterns were also observed herein.…”
supporting
confidence: 52%
See 3 more Smart Citations
“…The value of the antiradical capacity was found to reflect the antioxidant properties based on the hydrogen atom transfer mechanism [40,41,56,57]. A number of valuable patterns were also observed herein.…”
supporting
confidence: 52%
“…Determination of antioxidant capacity (AOC) was carried out by the potentiometric method using the oxidizing agent K 3 [Fe(CN) 6 ]. The use of potassium hexacyanoferrate (III) as an oxidizing agent is justified both from a thermodynamic point of view and from the point of view of obtaining an optimal analytical signal [40,41,[54][55][56]. An analytical signal, in this case, is the shift of the potential of the platinum electrode in the K 3 [Fe(CN) 6 ]/K 4 [Fe(CN) 6 ] system, which is observed when the analyzed sample is introduced (Figure S22).…”
Section: Potentiometric Assay Of Determining Antioxidant Capacitymentioning
confidence: 99%
See 2 more Smart Citations
“…26 Indeed, they were found to be good inhibitors, with avonoids, of peroxyl radicals. 27 Rutin and quercetin are considered from the most potent antioxidant agents and several studies 28,29 reported that these avonoids may considerably reduce oxidative stress and lipid peroxidation in brain, kidney and liver by enhancing the expression of key genes involved in antioxidant processes like glutathione S transferase a (GSTa), paraoxonase-1(PON-1) and glutamate-cysteine ligase (GCL). This process will considerably decrease the plasma level of malondialdehyde (MDA) and Glutathione (GSH) considered as the principal markers of oxidative stress.…”
Section: Scavenger Effect Of Extracts Against the Dpph Radicalmentioning
confidence: 99%